Candidiasis--do we need to fight or to tolerate the Candida fungus? - Raska, M; Bĕláková, J; Krupka, M; Weigl, E (Folia microbiologica, 2007)
Candidiases, infections caused by germination forms of the Candida fungus, represent a heterogeneous group of diseases from systemic infection, through mucocutaneous form, to vulvovaginal form. Although caused by one organism, each form is controlled by distinct host immune mechanisms. Phagocytosis by polymorphonuclears and macrophages is generally accepted as the host immune mechanism for Candida elimination. Phagocytes require proinflammatory cytokine stimulation which could be harmful and must be regulated during the course of infection by the activity of CD8+ and CD4+ T cells. In the vaginal tissue the phagocytes are inefficient and inflammation is generally an unwanted reaction because it could damage mucosal tissue and break the tolerance to common vagina antigens including the otherwise saprophyting Candida yeast. Recurrent form of vulvovaginal candidiasis is probably associated with breaking of such tolerance. Beside the phagocytosis, specific antibodies, complement, and mucosal epithelial cell comprise Candida eliminating immune mechanisms. They are regulated by CD4+ and CD8+ T cells which produce cytokines IL-12, IFN-gamma, IL-10, TGF-beta, etc. as the response to signals from dendritic cells specialized to sense actual Candida morphotypes. During the course of Candida infection proinflammatory signals (if initially necessary) are replaced successively by antiinflammatory signals. This balance is absolutely distinct during each candidiasis form and it is crucial to describe and understand the basic principles before designing new therapeutic and/or preventive approaches.
Keywords: T-lymfocyty; Immunity, Cellular; Immunity, Innate; Antifungal Agents; fagocytóza; Phagocytosis; přirozená imunita; antifungální látky; přenašečství; Carrier State; T-Lymphocytes; lidé; buněčná imunita; Candida; Candidiasis; Humans; kandidóza